ダイ 27 ジ エットウ タイ リクジョウ セイブツ チョウサ ホウコク(1986-1987) - 井上, 正鉄; イノウエ, マサカネ; 佐藤, 安弘; サトウ, ヤスヒロ; 内藤, 靖彦; ナイトウ, ヤスヒコ; Inoue, Masakane; Sato, Yasuhiro; Naito, Yasuhiko (1990)
P(論文) 第27次越冬隊(1986-1987)の生物・医学系が実施した陸上生物調査の概要, 及びラングホブデ雪鳥沢河口に建設された生物観測小舎の建設経過とそこを拠点とした調査活動, 生活全般について報告した。陸上生物調査は, 研究計画「南極陸上生態系構造の解析」の一環として地衣類の分類・生態学的研究に主眼を置いた。日の出岬からパッダに至る約300kmの範囲にかけて点在する大陸氷縁露岩と鳥嶼部49カ所を踏査し, 分類学的研究に供する大量のサンプルを得た。また, 昭和基地に近い西オングル島と, 小舎の建設により夏期間の長期滞在調査が可能になったラングホブデでは種々の生態学的研究を行った。生物観測小舎の建物は第27次観測隊の夏オペレーションで建設され, 内装その他の付帯作業は海氷の安定した6月に2次に分けて行われた。この小舎は厳冬期, 春期にはラングホブデ周辺域での調査拠点として, あるいはスカルブスネス, スカーレン方面への調査旅行の際の避難所, 補給所として有効に活用された。11月から翌年にかけての2ヵ月間におよぶ長期滞在は3名で円滑に行われた。 Records of field surveys of terrestrial biology, which were carried out from January 1986 to February 1987 as a link in the chain of the winter program of the 27th Japanese Antarctic Research Expedition (JARE-27), are briefly reported. A biological observatory hut was constructed at the mouth of the Yukidori Valley, Langhovde. In conjunction with a 5-year study of terrestrial Antarctic ecosystems in the ice-free areas near Syowa Station, a field survey for collecting lichens was carried out along the Soya Coast and Prince Olav Coast. Forty-nine areas were visited and a large number of samples were collected for a taxonomic study. In West Ongul Island near Syowa Station and Langhovde, where the hut was constructed and the party stayed there for 2 months, various ecological studies were carried out. departmental bulletin paper